On dreaming a different world together? - Smit, Dirk J (Stellenbosch Theological Journal, 2023)
The article provides some broad perspectives on what is happening in the global Reformed world today. It takes its point of departure in two recent editions of the Reformed World, the official journal of the World Communion of Reformed Churches that is again being published since 2021 after a short interruption in publication. It shows how these editions embody the present self-description of the global body, namely “Called to Communion; Committed to Justice” as well as its strategic vision, “Confessing the God of Life in a World Fallen Among Thieves.” In this process, a brief overview is offered of distinct Reformed emphases in four of the most important bilateral reports in which the World Communion participated in recent years. Based on this overview, four brief theological observations conclude the broad picture.